Comparative Transcriptome Analysis Identifies Putative Genes Involved in the Biosynthesis of Xanthanolides in Xanthium strumarium L. - Li, Yuanjun; Gou, Junbo; Chen, Fangfang; Li, Changfu; Zhang, Yansheng (Frontiers in Plant Science, 2016)
Xanthium strumarium L. is a traditional Chinese herb belonging to the Asteraceae family. The major bioactive components of this plant are sesquiterpene lactones, which include the xanthanolides. To date, the biogenesis of xanthanolides, especiallytheir downstream pathway, remains largely unknown. In X. strumarium, xanthanolides primarily accumulate in its glandular trichomes. To identify putative gene candidates involved in the biosynthesis of xanthanolides, three X. strumarium transcriptomes, which were derived from the young leaves of two different cultivars and the purified glandular trichomes from one of the cultivars, were constructed in this study. In total, 157 million clean reads were generated and assembled into 91,861 unigenes, of which 59,858 unigenes were successfully annotated. All the genes coding for known enzymes in the upstream pathway to the biosynthesis of xanthanolides were present in the X. strumarium transcriptomes. From a comparative analysis of the X. strumarium transcriptomes, this study identified a number of gene candidates that are putatively involved in the downstream pathway to the synthesis of xanthanolides, such as four unigenes encoding CYP71 P450s, 50 unigenes for dehydrogenases, and 27 genes for acetyltransferases. The possible functions of these four CYP71 candidates are extensively discussed. In addition, 116 transcription factors that were highly expressed in X. strumarium glandular trichomes were also identified. Their possible regulatory roles in the biosynthesis of sesquiterpene lactones are discussed. The global transcriptomic data for X. strumarium should provide a valuable resource for further research into the biosynthesis of xanthanolides.